2003
DOI: 10.4067/s0717-65382003000200013
|View full text |Cite
|
Sign up to set email alerts
|

Marine biodiversity in French Guiana: Estuarine, coastal, and shelf ecosystems under de influence of Amazonian waters

Abstract: Marine biodiversity in French Guiana is strongly influenced by the amagon River waters of the river Amazon, which constitute a major structuring factor for the estuarine, coastal, and shelf marine ecosystems. Moreover, the marked seasonal and interannual variabilities play important roles in the stability or fluctuations in the environmental parameters that influence biodiversity at the ecological, population, and genetic levels. Previous and ongoing studies of the marine and littoral biota relate mostly to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
(14 reference statements)
0
37
0
2
Order By: Relevance
“…This scarcity of reports is not due to the lack of studies on Neotropical mangrove ecosystems, which have increased drastically in the past 30 years. Many studies have reported the presence of U. cordatus in other areas, e.g., Belize (Middleton and McKee 2001;McKeon and Feller 2004), Jamaica (Warner 1969), Costa Rica (Delgado et al 2001), Panama (Sousa et al 2003), Colombia (Cantera et al 1999), French Guyana (Artigas et al 2003). However, the biology of this crab has seldom been studied outside Brazil, probably due to either a lack of understanding of its importance in mangrove forests or the absence of large U. cordatus populations as in Brazilian forests.…”
Section: Introductionmentioning
confidence: 95%
“…This scarcity of reports is not due to the lack of studies on Neotropical mangrove ecosystems, which have increased drastically in the past 30 years. Many studies have reported the presence of U. cordatus in other areas, e.g., Belize (Middleton and McKee 2001;McKeon and Feller 2004), Jamaica (Warner 1969), Costa Rica (Delgado et al 2001), Panama (Sousa et al 2003), Colombia (Cantera et al 1999), French Guyana (Artigas et al 2003). However, the biology of this crab has seldom been studied outside Brazil, probably due to either a lack of understanding of its importance in mangrove forests or the absence of large U. cordatus populations as in Brazilian forests.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, salutary marine habitat is largely absent from the Guianese continental shelf, where the Amazon plume creates a 10 m deep surface layer of turbid low-salinity water (Artigas et al, 2003) and deposits 5 m thick mud-banks that extend offshore to the 20 m isobath (Allison et al, 2000). In fact, salutary marine habitat is largely absent from the Guianese continental shelf, where the Amazon plume creates a 10 m deep surface layer of turbid low-salinity water (Artigas et al, 2003) and deposits 5 m thick mud-banks that extend offshore to the 20 m isobath (Allison et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…7). While Bagre bagre is extremely common in the region influenced by the Amazon Plume (Le Bail et al, 2000;Artigas et al, 2003), B. marinus is rare or absent from this area (Pinheiro et al, 2006;Garcia Júnior et al, 2010) (Fig. 7).…”
Section: Discussionmentioning
confidence: 96%
“…Bagre bagre is an important fishery resource in northern Brazil (Pinheiro & Fredou 2004;Isaac-Nahum, 2006), as well as the Guianas and Suriname (Le Bail et al, 2000;Artigas et al, 2003), but is rare or absent from commercial catches on the eastern and southeastern coast of Brazil (Freitas Netto et al, 2002;Lopes et al, 2002). The adequate definition of a species is a decisive step in the evaluation of its conservation status, and the development of effective management strategies (Marceniuk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%